Diamonds are forever [videorecording (DVD)] - Hamilton, Guy, 1922-2016; Connery, Sean; St. John, Jill; Gray, Charles D., 1928-2000; Fleming, Ian, 1908-1964
Agent 007 infiltrates a diamond smuggling ring to stop his nemesis Bloefeld from building a deadly satellite laser.